Challenges Faced by Non-Islamic Boarding School Students in Drilling Arabic Program - Dzulqornain, Rofiah; Anwar, Najih (Indonesian Journal of Islamic Studies, 2023)
This qualitative study examines the difficulties encountered by non-Islamic boarding school students, particularly X-grade alumni, in engaging in muhadatsah (dialogue) within the Drilling Arabic Program (DAP) curriculum at MA Bilingual Junwangi. The research employed a case study approach, involving interviews, observations, and documentation, with DAP instructors and selected X-grade alumni as research subjects. Data analysis comprised data reduction, categorization, presentation, and conclusion drawing. The study revealed three stages in DAP instruction: preparation, implementation, and evaluation. Challenges faced by students included inadequate understanding of DAP content, limited grasp of Arabic language rules, instructor and peer factors, and insufficient time allocation. MA Bilingual offered solutions such as supplementary DAP assignments, additional programs at Islamic boarding schools, substitute instructors with similar expertise, student-level conditioning, and differentiated timing for additional programs. The findings contribute to understanding the challenges faced by non-Islamic boarding school students in DAP and provide insights for curriculum improvement and instructional strategies in Arabic language education. Highlight: The study investigates the challenges faced by non-pesantren students in the implementation of the Drilling Arabic Program (DAP) at MA Bilingual Junwangi, focusing on X-grade alumni. The research employs a qualitative case study approach, utilizing interviews, observations, and documentation to collect data from DAP instructors and X-grade alumni. The findings reveal difficulties in understanding DAP content, Arabic language rules, instructor and peer factors, and time constraints. MA Bilingual offers solutions such as additional assignments, supplementary programs, expert substitute instructors, leveled student conditioning, and differentiated program timing. Keyword: Drilling Arabic Program, Non-Pesantren Students, Challenges, Solutions, Qualitative Study